Occurrence of Antimicrobial-Resistant Enterococcus spp. in Healthy Chickens Never Exposed to Antimicrobial Agents in Central Italy - Giulia Cagnoli; Alessia Di Paolo; Fabrizio Bertelloni; Sonia Salvucci; Arianna Buccioni; Margherita Marzoni Fecia di Cossato; Valentina Virginia Ebani (MDPI AG, 2024)
Enterococci are part of the natural flora of the gastrointestinal tract of mammals, including humans, birds and invertebrates. They can cause infection, mainly among hospitalized patients, as well as acquire and transfer antimicrobial resistance genes. The present study allowed the isolation of 98 Enterococcus (73.47% E. faecium, 23.47% E. faecalis, 3.06% E. avium) strains from 120-day-old healthy chickens that had never been treated with antimicrobials. Their antimicrobial resistance was evaluated by the agar disk diffusion method; high-level aminoglycoside (streptomycin and gentamicin) and vancomycin resistance were established using the microbroth dilution method. The highest percentages of resistant isolates were detected with quinupristin-dalfopristin (88.78%), rifampicin (64.29%), tetracyclines (45.92%), and enrofloxacin (41.84%). High percentages of susceptible strains were found with teicoplanin (100%), amoxicillin-clavulanic acid (97.96%), nitrofurantoin (94.90%), ampicillin (92.86%), chloramphenicol (90.82%), and linezolid (88.78%). About 60% of the strains were classified as MDR (multidrug-resistant). Moreover, PCR was carried out to investigate genes encoding for tetracyclines resistance determinants: tet(M), tet(L), tet(O), tet(K), and Int-Tn. Genes were detected in 68 (69.38%) strains: 36 were shown to be resistant with the agar disk diffusion method, while 28 were intermediate, and 2 were susceptible. The present study showed that chickens never treated with antimicrobials potentially harbor enterococci having phenotypic and genotypic characters of antimicrobial resistance.